2010
DOI: 10.3858/emm.2010.42.6.047
|View full text |Cite
|
Sign up to set email alerts
|

Role of phospholipase D1 in glucose-induced insulin secretion in pancreatic β cells

Abstract: Abbreviations: BFA, Brefeldin A; mTOR, mammalian target of rapamycin; p70S6K, p70 ribosomal S6 kinase AbstractAs glucose is known to induce insulin secretion in pancreatic β cells, this study investigated the role of a phospholipase D (PLD)-related signaling pathway in insulin secretion caused by high glucose in the pancreatic β-cell line MIN6N8. It was found that the PLD activity and PLD1 expression were both increased by high glucose (33.3 mM) treatment. The dominant negative PLD1 inhibited glucose-induced B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…We also demonstrated that H-Ras-induced PLD activity was dependent on ARF6 (40). ARF6 has also been implicated in the glucose stimulation of insulin secretion (19), indicating that ARF6 is activated in response to nutrients. Thus, the involvement of RalA, in the amino acid-and glucose-dependent PLD activity shown in Fig.…”
Section: Pld Activity In Human Cancer Cells Is Dependent On Aminomentioning
confidence: 62%
See 3 more Smart Citations
“…We also demonstrated that H-Ras-induced PLD activity was dependent on ARF6 (40). ARF6 has also been implicated in the glucose stimulation of insulin secretion (19), indicating that ARF6 is activated in response to nutrients. Thus, the involvement of RalA, in the amino acid-and glucose-dependent PLD activity shown in Fig.…”
Section: Pld Activity In Human Cancer Cells Is Dependent On Aminomentioning
confidence: 62%
“…Our data are consistent with this model in that there is agreement that Rheb is critical for the activation of mTORC1 in response to amino acids. However, our study also takes into account previous studies linking the nutrient response of mTORC1 to RalA (12), ARF6 (19), and hVps34 (22)(23)(24)(25). A common denominator for all three of these factors is PLD and a direct link to mTORC1 through PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The translocation of ARF6 stimulates PLD1 [113] and PLD2 [108] in vivo. The importance of ARF protein exemplified by ARF1 is proved by its necessity for the activation of PLDs.…”
Section: +mentioning
confidence: 99%